Characterization of Six Common Household Pollutants in Multilayered Indoor Air Quality System for Monitoring and Reducing Volatile Organic Compounds and PM2.5 - Glenn V. Magwili; Mathew G. Bandiez; Jobert A. Carbon (Engineering Proceedings)
Air pollution is a significant health concern identified by the World Health Organization (WHO) as it poses serious health risks and climate impacts. WHO indicates that 99% of the global population breathes air with pollutant levels exceeding safe guidelines. Indoor particulate level (IPL) is approximately 20% higher in naturally ventilated buildings than mechanically ventilated ones. Volatile organic compounds (VOCs), found in products such as pesticides and gasoline, and pollutants including PM2.5 and PM10 contribute to these health risks. This study aims to characterize six common household pollutants, focusing on their concentrations and potential health impacts indoor environments. By understanding the characteristics of the pollutants, indoor air quality can be improved to mitigate associated health risks. The results showed that VOC showed the highest level of concentration as 23.8% was filtered while vape showed the highest concentration of PM2.5 with 83.3% filtered. No significant difference was observed among the VOC concentrations of candles, mosquito coils, and cigarettes. For PM2.5, frying and LPG had the same levels of concentration while the other groups had similar levels.